A case‐control emergency department‐based analysis of acute pancreatitis in Covid‐19: Results of the UMC‐19‐S6. (7th January 2021) - Miró, Òscar; Llorens, Pere; Jiménez, Sònia; Piñera, Pascual; Burillo‐Putze, Guillermo; Martín, Alfonso; Martín‐Sánchez, Francisco J; Lamberechts, Jorge; Alquézar‐Arbé, Aitor; Jacob, Javier; Noceda, José; Cano Cano, María J; et al.
Abstract: Background/Purpose: We investigated the incidence, risk factors, clinical characteristics and outcomes of acute pancreatitis (AP) in patients with COVID‐19 attending the emergency department (ED), before hospitalization. Methods: We retrospectively reviewed all COVID patients diagnosed with AP in 62 Spanish EDs (20% of Spanish EDs, COVID‐AP) during the COVID outbreak. We formed two control groups: COVID patients without AP (COVID‐non‐AP) and non‐COVID patients with AP (non‐COVID‐AP). Unadjusted comparisons between cases and controls were performed regarding 59 baseline and clinical characteristics and four outcomes. Results: We identified 54 AP in 74 814 patients with COVID‐19 attending the ED (frequency = 0.72‰, 95% CI = 0.54‐0.94‰). This frequency was lower than in non‐COVID patients (2231/1 388 879, 1.61‰, 95% CI = 1.54‐1.67; OR = 0.44, 95% CI = 0.34‐0.58). Etiology of AP was similar in both groups, being biliary origin in about 50%. Twenty‐six clinical characteristics of COVID patients were associated with a higher risk of developing AP: abdominal pain (OR = 59.4, 95% CI = 23.7‐149), raised blood amylase (OR = 31.8; 95% CI = 1.60‐632) and vomiting (OR = 15.8, 95% CI = 6.69‐37.2) being the strongest, and some inflammatory markers (C‐reactive protein, procalcitonin, platelets, D‐dimer) were more increased. Compared to non‐COVID‐AP, COVID‐AP patients differed in 23 variables; the strongest ones related to COVID symptoms, but less abdominal pain was reported, pancreatic enzymes raise was lower, and severity (estimated by BISAP and SOFA score at ED arrival) was higher. The in‐hospital mortality (adjusted for age and sex) of COVID‐AP did not differ from COVID‐non‐AP (OR = 1.12, 95% CI = 0.45‐245) but was higher than non‐COVID‐AP (OR = 2.46, 95% CI = 1.35‐4.48). Conclusions: Acute pancreatitis as presenting form of COVID‐19 in the ED is unusual (<1‰ cases). Some clinically distinctive characteristics are present compared to the remaining COVID patients and can help to identify this unusual manifestation. In‐hospital mortality of COVID‐AP does not differ from COVID‐non‐AP but is higher than non‐COVID‐AP, and the higher severity of AP in COVID patients could partially contribute to this increment. Abstract : Highlight Miró and colleagues found that acute pancreatitis was less frequent in COVID patients than in non‐COVID patients attending the emergency department, suggesting the absence of a direct relationship with SARS‐CoV‐2. This report is the first to present the distinctive characteristics of COVID patients at increased risk of presenting acute pancreatitis.